Emotional Intelligence Level Relationship with Santri Compliance Applying Pesantren Rules - Waslah Waslah; Nur Ismianah (SCHOOLAR: Social and Literature Study in Education, 2022)
emotional is a must that belongs to every student. in boarding schools have rules and regulations, as students must be able to comply with the established by the nanny boarding school al-huda. emotional intelligence santri very instrumental to comply with the existing rules dipondok Islamic boarding school, exemplary students have high emotions to run the rules of the cottage. This study uses a quantitative approach with santri respondents from one of the mondok in pondok Islamic boarding school al-huda. aims to how much the relationship of emotional intelligence level with the compliance of students in carrying out the rules of boarding school Al-huda the purpose of this study is to find out that there is a relationship of santri with emotional intelligence in carrying out the rules of the cottage. this study uses statistical test data of SPSS program. The results of this study prove that emotional intelligence has a positive and significant effect on the compliance of students in running Islamic boarding school huts.